Radiation Tolerance Testing Methodology of Robotic Manipulator Prior to Nuclear Waste Handling - Zhang, Kaiqiang; Hutson, Chris; Knighton, James; Herrmann, Guido; Scott, Tom (Frontiers in Robotics and AI, 2020)
Dramatic cost savings, safety improvements and accelerated nuclear decommissioning are all possible through the application of robotic solutions. Remotely-controlled systems with modern sensing capabilities, actuators and cutting tools have the potential for use in extremely hazardous environments, but operation in facilities used for handling radioactive material presents complex challenges for electronic components. We present a methodology and results obtained from testing in a radiation cell in which we demonstrate the operation of a robotic arm controlled using modern electronics exposed at 10 Gy/hr to simulate radioactive conditions in the most hazardous nuclear waste handling facilities.